Let's break down the problem:
- Let \( a \) be Tony's current age.
- Since Andrea is 6 years younger than Tony, her current age is \( a - 6 \).
- In two years, Tony's age will be \( a + 2 \) and Andrea’s age will be \( (a - 6) + 2 = a - 4 \).
According to the problem, in two years, Tony will be three times as old as Andrea, which gives us the equation:
\[ a + 2 = 3(a - 4) \]
Now, let's manipulate this equation:
-
Expand the right side: \[ a + 2 = 3a - 12 \]
-
Rearranging gives: \[ 2 + 12 = 3a - a \] \[ 14 = 2a \] \[ a = 7 \]
So, the equation we derived that relates Tony’s and Andrea's ages is \( a + 2 = 3(a - 4) \).
Now, let's see which of the options fits:
- \( a = 3(a + 2) \) → Incorrect
- \( 3(a + 2) = a - 6 + 2 \) → Incorrect
- \( a + 2 = 3(a - 6 + 2) \) → Correct (this is equivalent to our equation)
- \( a + 2 = 3(a + 6 + 2) \) → Incorrect
Thus, the correct equation that can be used to find Andrea’s and Tony’s current ages is:
Option 3: \( a + 2 = 3(a - 6 + 2) \)